Analisis Perubahan Kurikulum 2013 Ke Kurikulum Merdeka Belajar Dalam Kinerja Guru - Gisela Adisti Listianto; Putri Ayu Romadhotin; Muhammad Ridho Maulana; Ayu Wulandari; Syunu Trihantoyo; Kaniati Amalia (Universitas 45 Surabaya, 2023)
This study was conducted at the school sdn west language 1 surabaya, by interviewing one of the teachers. This study aims to analyze any challenges that occurred during the 2013 change to the independent learning curriculum to teacher performance. The method used in the observation this time using qualitative methods, by interviewing one of the 5th grade teacher sd who has implemented an independent curriculum.This type of research data is using data collection techniques such as interviews with subjects needed in research as well as school data documentation needed in research. Results of research conducted at sdn lidah barat 1 surabaya this results analysis of change curriculum 2013 to independent curriculum study in teacher performance at sdn lidah barat 1 is still in the adjustment stage because the independent curriculum is a new curriculum, So the new teacher tried to teach an independent curriculum to the students in this in March initially with classes 1 and 4.In addition to the new first option to implement this independent curriculum.Teacher and learners alike need to understand the independent curriculum and still adjustment stage.Which goes back to the curriculum 2013 in exchange for an independent curriculum because learning is simpler and easier to understand.The achievement standards of the independent curriculum are simpler than the curriculum 2013, The materials given are also less, so that it can give time for the teacher to dive into each of his concepts.